PENGARUH PROFITABILITAS, SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN DI BURSA EFEK INDONESIA - Tuladang, Devika Oktavia; Tipa, Handra (SCIENTIA JOURNAL, 2020)
This researh is expected to provide basic information to investors regarding timeliness financial reporting that will be relevant information for investors in business and economic decision making. Based on the case that occurred on the IDX there are several companies that have not published financial statements and have not paid late fees as of December 31, 2018, but in terms of investment growth shows an increased in investment growth from 2017-2018. In line with the increase in investment, of course investors need relevant and timely information because the capital market moves dynamically every minutes. The population in this research is the financial reporting of financial institution in IDX from 2016-2019. Based on sample criteria, there are 56 samples. The results of profitability and solvability of research partially have a significant effect on audit report lag while company size has no significant effect on the timeliness of financial reporting. From the results of the F test it can be seen that the Fcount is compared with Ftable 5,565 > 3,17 and a significant value of 0,002 < 0,05 which simultaneously shows the profitability, solvability and company size have a significant effect on audit report lag.